Differences between FEV6, FVC and VC at the diagnosis of obstructive ventilatory defect - Sousa, C.S. (2022)
Introduction: The diagnosis of airway obstruction can be made through FEV1/FVC ratio <0.7 or FEV1/VC ratio < lower limit of normality (LLN). Several authors advocate that FEV1/FEV6 ratio is an alternative to diagnosing obstructive ventilatory defect, while others have determined that the best cut-off for this ratio (best combined sensitivity and specificity) is 0.73. Objective: To evaluate the non-inferiority of FEV1/FEV6 ratio < 0.73 when compared to FEV1/ FVC ratio < 0.7 and FEV1/VC < LLN in diagnosing airway obstruction. Methods: A retrospective analysis of the medical records from patients who underwent spirometry or plethysmography in a university central hospital from June 1st to December 31st, 2018 was carried out. Only medical records which included FEV1/FVC < 0.7 or FEV1/VC < LLN were selected, and these results were compared to FEV1/FEV6 ratio. Results: A total of 526 patients with obstructive ventilatory defect were identified by one of the two ratios described. Of these, 95.1%, 87.4% and 88.6% were obstructive by FEV1/FVC, FEV1/ VC, and FEV1/FEV6 ratio, respectively. The positive predictive value (PPV) of FEV1/FEV6 in relation to FEV1/FVC ratio was 99.6% (p < 0.001) with a diagnostic efficacy of 92.8%, whereas the PPV of FEV1/FEV6 in relation to FEV1/VC was 91.0% (p < 0.001) and diagnostic efficacy was 85.2%. Most false negatives, comparing FEV6 with the other two tests, were found in patients with FEV1 > 70% (mild obstruction) and in individuals aged >50 years. Conclusions: FEV1/FEV6 < 0.73 may be a good alternative ratio, as it is non-inferior to FEV1/VC and FEV1/FVC in diagnosing obstructive ventilatory defect.